Análise cartográfica da eleição presidencial de 2018 - Hervé Théry (Confins)
The results of the presidential election of October 28, 2018 are analysed using thematic cartography. After processing of various types of data, obtained from official and unofficial sources, traditional variables or more innovative indicators. Multivariate analyses (factorial and cluster analysis) are used for the elaboration of cartographic syntheses. Maps are then interpreted, commented and linked to the elementary structures of the territory (Théry, 1986) still valid because nothing is more resilient than these fundamental structures. Their combination accounts for the observed complexity and its dynamics, with territorial contradictions and conflicts also being identified in the spatialization of data.